World survey of civil aviation. - United States. Business and Defense Services Administration (Washington, 1960)
v.1.Japan.--v.2.Africa.--v.3.Southwest Asia.--v.4.Near and Middle East.--v.5.Selected Asian countries and Oceania.--v.6.Mexico, Central America, and the Caribbean area.--v.7.South America.--v.8.Denmark, Finland, Iceland, Norway, Seden.--v.9.United Kingdom.--v.10.Continental Europe and Ireland.--v.11.Japan.--v.12.Canada. Mode of access: Internet.